StreptInCor, a Group A Streptococcal Adsorbed Vaccine: Evaluation of Repeated Intramuscular Dose Toxicity Testing in Rats - de Sá-Rocha, Luiz Carlos; Demarchi, Lea Maria Macruz Ferreira; Postol, Edilberto; Sampaio, Roney Orismar; de Alencar, Raquel Elaine; Kalil, Jorge; Guilherme, Luiza (Frontiers in Cardiovascular Medicine, 2021)
Streptococcus pyogenes infections continue to be a worldwide public health problem, causing various diseases in humans, with rheumatic fever and rheumatic heart disease being the most harmful manifestations. Impetigo and poststreptococcal glomerulonephritis are also important sequelae of skin infections. We have developed a candidate vaccine epitope (StreptInCor) that presents promising results in diverse animal models. To assess whether the StreptInCor adsorbed vaccine could induce undesirable effects, a certified independent company conducted a repeated intramuscular dose toxicity evaluation in Wistar rats, a choice model for toxicity studies. We did not observe significant alterations in clinical, hematological, biochemical, anatomical or histopathological parameters or in cardiac function due to vaccine administration, even when the animals received the highest dose. In conclusion, repeated intramuscular doses did not show signs of macroscopic or other significant changes in the clinical or histopathological parameters, indicating that StreptInCor can be considered a safe candidate vaccine.